To Close is Impossible to Leave it: Where Should be Put a Comma? - E. A. Pleshkevich (Библиосфера)
The article is a response to the article by V. K. Stepanov “A great reduction in quantity of libraries: particular management errors or a general perspective for the field (analysis of the experience of the Moscow region)”, published in the previous issue of Bibliosphere. Three main theoretical and methodological contradictions that reduce the reliability of the results obtained by the author and the validity of the recommendations proposed by him for regional librarianship are identified and analyzed.The first of them concerns the departure from the principle of historicism, as well as the complexity of the consideration of the phenomenon under study, and as a result the social nature of librarianship is presented incorrectly by the author of the article. It is noted that the basic social function determining the vector of domestic library construction was the function of educating a Soviet person, his ideological, cultural, scientific and technical enlightenment through the guidance of book reading in a specially selected library fund. Intermediary functions were associated with the shortcomings of book publishing in the field of leisure literature and played a secondary role. Thus, automation and computerization of book publishing and bookselling affect librarianship only indirectly, since the material nature of book publishing does not affect the cultural and educational functions of libraries.The second contradiction is related to the correctness of the analysis and interpretation of statistical data reflecting the process of library development in the Moscow region. The analysis of statistics shows that the negative dynamics in regional library construction is caused by the process of reduction of settlements, its natural decline and aging of the population. The increase in the number of users of municipal libraries indicates that the reduction in the number of libraries does not lead to a decrease in the level of library services of the population.The third contradiction concerns following the principle of scientific objectivity of research. The author noted only negative trends, leaving regional library construction programs aimed at the development of model libraries outside the scope of his analysis.